Comparative Study of Machine Learning Techniques for Insurance Fraud Detection - Duwadi, Navin; Sharma, Anita (Institut Teknologi Dirgantara Adisutjipto, 2024)
Insurance fraud has been a constant presence in the realm of insurance. However, as strategies and methods for committing insurance fraud have evolved, the frequency and volume of such fraudulent activities have also increased. An example of this is vehicle insurance fraud, which involves collaborating to fabricate false or exaggerated claims related to property damage or personal injuries resulting from an accident. Machine learning techniques seems to be more beneficial and great way to address the fraud in the insurance industry. This paper comprehensively examines existing research through a systematic literature review. This review aims to identify previously attempted approaches and evaluate which machine learning algorithm is best suited for this specific problem. This paper proposes a methodology for identifying fraudulent insurance claims. This approach can significantly improve efficiency and cost savings for insurance companies in handling such cases. The most popular traditional machine learning algorithms used to identify insurance fraud in the auto industry were found to be support vector machine, logistic regression, and random forest.